La estancia en Granada de la familia Fortuny-Madrazo - Nicolás Martínez, María del Mar (Cuadernos de arte de la Universidad de Granada, 1990)
From July 1870 to October 1872 Mariano Fortuny and his family lived in Granada, together with Ricardo de Madrazo Garreta. They were extremely active here, and this period is of considerable importance in their personal and professional lives. A study of unpublished letters written by Richard and Cecilia de Madrazo to they father Federico, allows us to discover many of the most interesting events which occurred during this period. The letters provide news of riembers of the family, of their friends, the writer's views of Granada and its inhabitants, frank opinions of prominent public figures in the town, etc.